Analisis Penjualan Tedong dan Hubungannya dengan Kebudayaan Lokal di Pasar Bolu - Abdul Mannan; Nurmuti’a Hasfar; Nurledy Amandha; Anugerah Dwiputra Yuga; A. Fahrul Fakhrurrazy (Indonesian Journal of Fundamental and Applied Geography, 2024)
Production costs are the main factor in determining prices. Although, for some commodities, this does not apply. For art objects, the price is not determined by production costs, but rather by the value of the object. Toraja people have a unique view of buffalo. They believe that buffalo have value in Toraja customs, so the price of buffalo in Toraja is higher than in other areas. This price determination is of course based on the characteristics of the Toraja buffalo. Culture is an integrated part of community life. No society does not have culture as part of its characteristics. The research method used was direct interviews with buffalo breeder sources. The results of this research show how important buffalo are in the traditional ceremonies of the Toraja people. The high price of buffalo has an impact on ecological and social aspects, because striped buffalo (bonga) breeders will continue to ensure the availability of striped buffalo (bonga). It is needed so that traditional Toraja ceremonies which require striped buffalo (bonga) can continue to be carried out by the Toraja people.